Midsummer and Midwinter in the Rock Carvings of South Scandinavia - RICHARD BRADLEY (Temenos, 2008)
The article considers the light shed on ancient religion by comparative linguistics and the analysis of visual images. Its starting point is the Bronze Age 'Sun Chariot' from Trundholm in Denmark, which is considered in both Flemming Kaul's book Ships on Bronzes and Martin West's Indo-European Poetry and Myth. The ideas of these two writers are discussed in conncection with the evidence of prehistoric rock carvings in South Scandinavia. The article considers how such places were used and draws attention to the distinctive practice of depicting pairs of footprints in this medium. The footprints may mark the positions of people engaged in rituals at these sites, for in many cases the drawings are oriented towards the solstices. Perhaps these events were observed from the decorated outcrops. Although the field evidence is limited, it supports the idea of a solar cosmology postulated by Kaul and West.